The Effect of Strengthening of the Upper Limb, on Balance and Gait, in Old People Post-Stroke: Systematic Review - Figueiredo, Vânia (2023)
Introduction: The occurrence of stroke is higher in the elderly population, and 30% to 60% have upper limb (UL) limitations. The decrease of range of motion on the upper limb joints and pendular movement can lead to changes in gait pattern, risk of falling, and balance. Studies refer that UL strengthening benefits gait and functional capacity in patients with stroke sequels. Our aim was to determine the effect of strengthening of the UL, in adults aged 65 years or over and post-stroke, on gait, falls and standing balance. Methods: A search of the current literature was performed using PubMed, Cochrane Library and ScienceDirect, including randomized clinical trials, with no date limitation, evaluating the effect of UL strengthening on gait, falls and balance in post-stroke individuals aged 65 years or over. Two blinded reviewers, screened the articles for inclusion, with a third review in case of disagreement. Protocols, presentations, and articles with scores lower than 5 on the PEDro scale were excluded. Results: Six studies were included, with a total of 468 participants. Strengthening the MS is positively interferes with walking ability, namely at the level of speed, it acts in the prevention of falls, and shows improvements in balance, compared to baseline.   Conclusion: The inclusion of UL strengthening interferes positively in improving gait speed and balance, with the consequent reduction in the risk of falling in this population.